Fracture-Associated Microbiome and Persistent Nonunion: Next-Generation Sequencing Reveals New Findings. (February 2022) - Goswami, Karan; Tipton, Craig; Clarkson, Samuel; Chang, Gerard; Tan, Timothy L.; Fram, Brianna; Chisari, Emanuele; Sobol, Keenan; Natoli, Roman M.; Conway, Janet D.; Altman, Gregory T.; Parvizi, Javad; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: Fracture nonunion remains a devastating complication and may occur for several reasons, though the microbial contribution remains poorly estimated. Next-generation sequencing (NGS) techniques, including 16S rRNA gene profiling, are capable of rapid bacterial detection within clinical specimens. Nonunion cases may harbor microbes that escape detection by conventional culture methods that contribute to persistence. Our aim was to investigate the application of NGS pathogen detection to nonunion diagnosis. Methods: In this prospective multicenter study, samples were collected from 54 patients undergoing open surgical intervention for preexisting long-bone nonunion (n = 37) and control patients undergoing fixation of an acute fracture (n = 17). Intraoperative specimens were sent for dual culture and 16S rRNA gene-based microbial profiling. Patients were followed for evidence of fracture healing, whereas patients not healed at follow-up were considered persistent nonunion. Comparative analyses aimed to determine whether microbial NGS diagnostics could discriminate between nounions that healed during follow-up versus persistent nonunion. Results: Positive NGS detection was significantly correlated with persistent nonunion, positive in 77% more cases than traditional culture. Nonunion cases were observed to have significantly increased diversity and altered bacterial profiles from control cases. Discussion: NGS seems to be a useful adjunct in identification of organisms that may contribute to nonunion. Our findings suggest that the fracture-associated microbiome may be a significant risk factor for persistent nonunion. Ongoing work aims to determine the clinical implications of isolated organisms detected by sequencing and to identify robust microbial predictors of nonunion outcomes. Level of Evidence: Diagnostic Level II. See Instructions for Authors for a complete description of levels of evidence.